Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae) - Gibson, Gary A. P. (Zootaxa, 2016)
The Neotropical genus Macreupelmus Ashmead (Eupelmidae: Eupelminae) is revised based on females, males being unknown for the genus. The genus is redescribed, its phylogenetic relationships within Eupelminae discussed, and the species keyed, described and illustrated through macrophotography. Nine species are recognized—Macreupelmus auranticrus n. sp., M. aurantispina n. sp., M. brasiliensis Ashmead 1896, M. crassicornis (Cameron 1884), M. dromedarius (Cameron 1884), M. erwini n. sp., M. granulosus n. sp., M. laticlavius n. sp., and M. nigrispina n. sp. Excluded from the genus are Macreupelmus baccharidis Kieffer 1910 (transferred to Brasema Cameron as B. baccharidis (Kieffer) n. comb.), Macreupelmus bekilyi Risbec 1952 (transferred to Reikosiella (Hirticauda Bouček) as Reikosiella (Hirticauda) bekilyi (Risbec) n. comb.), and Macreupelmus pulchriceps Cameron 1905 (transferred to Eupelmus Dalman as E. (Eupelmus) pulchriceps (Cameron) n. comb.). The latter name is recognized as the senior synonym of Cerambycobius cushmani Crawford 1908 n. syn., Cerambycobius townsendi Crawford 1912 n. syn., and Eupelmus cyaniceps amicus Girault 1916 n. syn. Lectotypes are designated for M. brasiliensis, M. dromedarius and E. pulchriceps.